2017
DOI: 10.3389/feduc.2017.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Survey Instrument to Assess Aboriginal and Torres Strait Islander Students’ Resilience and Risk for Self-Harm

Abstract: Background: Australian policies for Aboriginal and Torres Strait Islander well-being outline the importance of local community-based interventions; for adolescents, schoolbased programs have been identified as beneficial. However, there is a lack of localized data to determine levels of resilience and risk and thus whether programs are effective. This paper describes the challenges and opportunities in collaboratively designing and piloting a localized survey instrument to measure Indigenous students' resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Consistent with recommendations to ensure cultural and contextual relevance ( 32 ), the CYRM-28 was cross-culturally adapted for use in our study with Indigenous Australian boarding school students (years 7–12). A six phase participatory action research process was used that resulted in: tailoring the CYRM-28 for the contexts of the distinct environments of boarding school and remote communities; adding 11 site-specific items; addressing relevant wellbeing issues; and delivering it in ways that are appropriate to the literacy levels and age of the students [this phase of the project is detailed at ( 13 )]. That process established both content and face validity for the resultant T4S instrument which incorporates the CYRM-28 ( 13 ).…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with recommendations to ensure cultural and contextual relevance ( 32 ), the CYRM-28 was cross-culturally adapted for use in our study with Indigenous Australian boarding school students (years 7–12). A six phase participatory action research process was used that resulted in: tailoring the CYRM-28 for the contexts of the distinct environments of boarding school and remote communities; adding 11 site-specific items; addressing relevant wellbeing issues; and delivering it in ways that are appropriate to the literacy levels and age of the students [this phase of the project is detailed at ( 13 )]. That process established both content and face validity for the resultant T4S instrument which incorporates the CYRM-28 ( 13 ).…”
Section: Aimmentioning
confidence: 99%
“…There are a range of survey instruments available internationally to measure resilience for both the general population and youth ( 9 11 ). However, they are rarely or inconsistently used to inform decision-making in health and education services for Indigenous youth ( 12 ) for reasons that include: concerns about risk based questions and their potential impact on students; lack of resourcing for services to conduct intervention-based research; concerns over the capacity to respond to mental health issues raised by the instrument, and; concerns over the appropriateness and relevance of international instruments for utility with Indigenous Australian youth ( 13 ). The suitability of international instruments for use with Indigenous Australian youth is also linked to broader concerns of data sovereignty—the production, ownership, and use of Indigenous data—and the cultural appropriateness of using standard measures in Indigenous contexts ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…An amended Transition Support Service Student Survey (T4S) instrument [24] was utilised. Amendments included use of the Kessler 6 instead of the Kessler 5 and a reduced Demographics: Participants' age, gender, and home community were included.…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on the health, healthcare service use and satisfaction of a cohort of Indigenous remote-dwelling north Queensland students who are required to attend boarding schools for secondary education because there is limited or no secondary schooling available in their home communities. It forms part of a broader ecological study to support and enhance the resilience of these students; other papers have provided a study protocol [22], descriptions of the survey development and validation [23,24], description of staff capacity development [25] and student survey baseline results [26]. Anecdotal evidence (2016) attained through this broader resilience study suggested that some students had untreated health conditions upon arrival at or during boarding school education, and/or experienced patchy care between remote home community and schoolbased healthcare services.…”
Section: Research and Theorymentioning
confidence: 99%
“…Here, social and emotional learning (SEL) programs provide a promising pathway. SEL programs have been effective in increasing resilience to adversity, improving mental health and reducing suicidal ideation [7,[15][16][17]. Research also indicates that SEL programs enhance social competence and academic success [18,19].…”
Section: Introductionmentioning
confidence: 99%